Entrepreneurial Ecosystems in Low-Density Regions: Business Incubation Practices in Alentejo - Rego, Conceição (2018)
Low density regions face many development challenges. In the Alentejo region of Portugal, and in many other Southern European regions, such challenges have been intensi ed by the cumulative e ects of the nancial and economic crises, and the subsequent austerity. In such context, and to promote region catching up and sustainable development, a number of policies designed to promote local entrepreneurial ecosystems have been reinforced. In this study, we focus on one of these policies’ instruments – business incubation - and on the region of Alentejo, and describe ve incubators implemented by a local regional development association (ADRAL), some municipalities, a national association of young entrepreneurs (ANJE), and a local association of entrepreneurs (NERE). We assess the incubators’ distinctive char- acteristics and those of some incubated projects, aiming at identifying the speci cities of this approach and its success determinants.